Expression of metalloproteinases 2 and 9 and tissue inhibitors 1 and 2 as predictors of lymph node metastases in oropharyngeal squamous cell carcinoma. Issue 3 (3rd April 2014) - Burduk, Pawel K.; Bodnar, Magdalena; Sawicki, Piotr; Szylberg, Łukasz; Wiśniewska, Ewa; Kaźmierczak, Wojciech; Martyńska, Maria; Marszałek, Andrzej
Abstract Background The matrix metalloproteinases (MMPs) and their tissue inhibitor of metalloproteinases (TIMPs) can decompose extracellular matrix (ECM) components and brake down basement membranes and, thus, promote tumor local invasion and metastasis. Methods We studied 41 patients with squamous cell carcinoma (SCC) of the oropharynx who underwent surgical treatment. Material was diagnosed by routine procedure and examined by immunohistochemical analysis and dot blot technique. We searched for correlations between expressions of MMPs, such as MMP‐2 and MMP‐9 and their tissue inhibitors TIMP‐1 and TIMP‐2 and treatment outcome. Results We found cytoplasmic expression of analyzed proteins, both in cancer cells and tumor stroma. The expression of analyzed antigens was higher in patients with lymph node metastases comparing patients without lymph node involvement. Conclusion Our data suggest that microenvironment changes are one of key factors in tumor progression. Divergent expression of MMPs and their inhibitors might be used as prognostic factor of oropharyngeal carcinoma progression. © 2014 Wiley Periodicals, Inc. Head Neck 37: 418–422, 2015